Social and obstetric inequalities and vaccination in pregnant women - Sara de Carvalho Oliveira; Thales Philipe Rodrigues da Silva; Gustavo Velásquez-Melendez; Larissa Loures Mendes; Eunice Francisca Martins; Edna Maria Rezende; Fernanda Penido Matozinhos (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to analyze the association of socioeconomic level and obstetric characteristics with vaccine registration of pregnant women. Methods: cross-sectional study, performed with 480 women in puerperal. Vaccination of pregnant women was considered a dependent variable and as independent variables were age, skin color, education, steady union, paid work, and number of prenatal consultations. Association between variables was verified by the Poisson's regression model. Results: from 480 pregnant women's health cards, 10.63% had information on hepatitis B vaccination; 31.46% for tetanus; and 90% of the health cards had not register for influenza. There was an association of paid work and number of prenatal consultations with hepatitis B vaccination. Conclusions: lower percentages in absence of vaccination occurred in women who were in the job market and had a higher number of prenatal consultations. This suggests that socioeconomic inequalities may interfere with the vaccination of pregnant women in health services.